Moderating Effects of Urbanization on Citizens’ Perception of Government Performance and Democratic Support in Sub-Saharan Africa - Nathan Teklemariam; Patricia Ng’ethe (Urban Science)
This study investigates the relationship between citizens’ perceptions of government socio-economic performance and support for democracy in sub-Saharan Africa (SSA), examining the moderating effect of urbanization rates. A quantitative approach was employed, using Afrobarometer survey data from 32 SSA countries; the research applies a moderation analysis to test these relationships. According to our findings, there is a negative association between perceived socio-economic performance and democratic support in SSA, which is contrary to modernization theory. Furthermore, urbanization rates significantly moderate this relationship, with the negative impact intensifying at higher urbanization levels. These findings suggest growing disillusionment with democracy’s ability to deliver socio-economic benefits in SSA, particularly in rapidly urbanizing areas where expectations may be higher. The study highlights the need to reconsider democratization dynamics in developing regions and underscores the importance of context-specific factors in shaping democratic attitudes. The findings suggest a need for governments and international organizations to focus on improving governance quality and service delivery, especially in urban areas, to maintain democratic support.